Skin-Immune-Neuro-Gastro-Endocrine (SINGE) System: Lighting the Fire on Atopic Dermatitis Research - Paz, Meshi; Lio, Peter (Dermatology Practical & Conceptual, 2025)
Introduction: Atopic dermatitis (AD) is a chronic inflammatory skin condition characterized by pruritic, dry, eczematous lesions. Traditionally regarded primarily as a cutaneous disorder influenced by genetic and environmental factors, AD is increasingly recognized as a multisystem condition involving immune, microbial, and neuroendocrine interactions. Objectives: This review proposes the Skin-Immune-Neuro-Gastro-Endocrine (SINGE) network as a comprehensive framework to explore the interconnected pathophysiology of AD. The aim is to highlight how changes across various systems contribute to disease development, presentation, and treatment. Methods: A comprehensive review of current literature was performed, examining the roles of skin barrier dysfunction, immune signaling, neuroendocrine pathways, and gut microbial dysbiosis. These domains were integrated into a unified model that describes bidirectional interactions and their clinical implications. Results: The SINGE model reveals that epidermal barrier disruption activates a cascade of immune responses. Microbial dysbiosis, in concert with the gut-skin axis, further exacerbates AD symptoms, highlighting how alterations in one organ affect the other. Neuroinflammation further contributes to AD symptoms by perpetuating the itch-scratch cycle. Neuroendocrine factors amplify the inflammatory dysregulation, particularly through endocrine involvement involving cortisol signaling in the hypothalamic-pituitary-adrenal (HPA) axis and the paradoxical inflammatory effects on the skin barrier. Together, these intertwined pathways perpetuate the chronic inflammation and skin barrier dysfunction in AD. Conclusion: By examining these elements as an intricate, intertwined system, the SINGE network reframes AD as a multisystem condition. This apprach not only shifts the understanding of the disease, but also serves as a foundation for exploration of targeted therapies.